2019
DOI: 10.1002/nop2.294
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions on fever management in children: A scoping review

Abstract: Background Numerous studies have been conducted specifically to target “fever phobia” and inappropriate fever management skills. However, despite educational intervention, caregivers continue to adopt inappropriate and non‐evidence‐based practices. Aims To collect and examine peer‐reviewed literature for active educational interventions aimed at improving fever management in children and profile them based on: who provided the training, training location, how the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
16
0
3
Order By: Relevance
“…This result confirms that fever phobic behaviours are significantly reduced when participant total knowledge is increased. This confirms previous reviews which hypothesize that attitudes and beliefs changes can be formed through the improvement of fever management knowledge 8,14,22 . Additionally, those that scored a higher score in Factor 2 – Patient Self Efficacy, predicated a higher knowledge score ( β = 0.277).…”
Section: Discussionsupporting
confidence: 87%
“…This result confirms that fever phobic behaviours are significantly reduced when participant total knowledge is increased. This confirms previous reviews which hypothesize that attitudes and beliefs changes can be formed through the improvement of fever management knowledge 8,14,22 . Additionally, those that scored a higher score in Factor 2 – Patient Self Efficacy, predicated a higher knowledge score ( β = 0.277).…”
Section: Discussionsupporting
confidence: 87%
“…Although the video can also be accessed later via the Info Library, it was not frequently used there. Considering earlier research proposing that although parents appear to prefer videos in comparison with other means of education [ 17 ], knowledge transfer remains a challenge even with informative videos. However, it could be that previous users already have, or believe they have, a basic knowledge that is sufficient for them, so that further immersion seems unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the influence of different manners of education regarding fever and found a positive outcome of attaining better knowledge and management of fevers [ 16 ]. However, in a scoping review, Arias et al [ 17 ] concluded that both parents and healthcare personnel should be addressed by a “more standardized educational platform”.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Arias et al, [22], illustrated in their study about an educational interventions on fever management in children, in Australia, that most interventions reported a positive impact in fever management skills. Also, this finding was similar to Bertille et al, [23] in their results in France, they reported that their recommendations about managing fever in children to parents were effective in changing the parents' practices with their children.…”
Section: Discussionmentioning
confidence: 93%